EFEKTIVITAS BUNDEL CATS DENGAN BUNDEL MODIFIKASI CATS TERHADAP PENURUNAN KEJADIAN INFEKSI DAERAH OPERASI PADA PASIEN OPERASI CAESARIA DI RSU MITRA MEDIKA TAHUN 2020 - Kartika Kuesno; Arifah Devi Fitriani; Deli Theo (Journal of Hospital Administration and Management (JHAM), 2024)
Background; Surgical Site Infection is an infection of the surgical wound or organs / space that occurs within 30 days after surgery or within 1 year if there is an implant. Sources of bacteria in SSI can derived from patients, doctors and teams, the environment, as well as the medical instrumental. Bundles are a set of valid evidence-based practices that result in improved health care outcomes when carried out collectively and consistently. Objectives; This study aims to compare the effectiveness of the CATS bundle with the modified CATS bundle on the incidence of SSI in caesarean surgery at Mitra Medika General Hospital. Methodology; The design of this study is quasi-experimental research, with a non-equivalent control group posttest - only design. The population in this study were 873 patients who underwent caesarean section surgery at Mitra Medika General Hospital. The sample of this study using purposive sampling, amount to 90 patients. Analysis of the data in this study using the Chi Square test. Results; The results of the Chi Square test analysis showed that the Fisher Exact p value was 0.167 . The p value was> 0.05, so H0 was accepted and H1 was rejected. Conclusions; The conclusion of this study is that there is no difference in the effectiveness of the CATS bundle and the modified CATS bundle on the incidence of SSI in caesarean section surgery patients at Mitra Medika General Hospital.